Edukasi Pada Ibu Hamil Untuk Mencegah Anemia - Winda Nurmayani M; Elisa Oktaviani; Dewi Nursukma Purqoti; Syamdarniati Syamdarniati (Poltekkes Kemenkes Surakarta, 2021)
Background: Anemia has a very negative effect, especially for babies in the womb, including it can cause miscarriage, babies born not quite months, babies are not fully developed, bleeding during childbirth, irregular contractions, disruption during the delivery process and susceptibility to infection can even result in a lack of production of breast milk. Methods: The implementation of community service activities is carried out in two different places because it is still in the COVID-19 pandemic period and to reduce crowds. Results: pregnant women who attended were very enthusiastic, after processing the questionnaire before and after the provision of health education, there was an increase in knowledge. Conclusion: Implementation of providing health education to increase knowledge for the community with risks that may occur with the condition of the community is very necessary to be done Apart from being an enhancer and an increase in knowledge, it is also an action to reduce the risk of health problems for the community